WORKFORCE AGILITY AND ADAPTIVE PERFORMANCE IN GOVERNMENT INSTITUTION: THE MEDIATING ROLE OF WORK ENGAGEMENT - Nur Ike Saptarini; Martina Dwi Mustika (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2023)
In government institutions, there have been several important changes such as the equalization of structural to functional positions and changes in the operating system. The state apparatus must have the ability to overcome changes and manage them. This research aims to determine how work engagement intervenes in the relationship between workforce agility and adaptive performance. The research was conducted quantitatively using a set of questionnaires. Participants in this study included 191 state apparatus in a government institution. The data was processed using IBM SPSS version 26. The mediating function of work engagement was examined using Andrew Hayes' analysis of the mediation model 4 Hayes process v4.0. The mediation test showed that the indirect effect of the range of confidence values is in the value 0.1448 – 0.4471 with a 95% confidence interval (CI) level and 5000 sample bootstraps. This suggests that the link between workforce agility and adaptive performance had a mediating role for work engagement variables. Based on this study, government institutions need to create employee development programs that can increase workforce agility and work engagement to improve the adaptive performance of state apparatus.